2019
DOI: 10.1371/journal.pone.0221980
|View full text |Cite
|
Sign up to set email alerts
|

The intensity of male-male competition may affect chemical scent constituents in the dark ventral patch of male Iberian red deer

Abstract: During the mating season, Iberian red deer males ( Cervus elaphus hispanicus ) present a large visible dark ventral area in their abdomen. This characteristic dark-haired area is formed by the impregnation of the hair with sprayed urine and gland secretions and contains volatile compounds that can be used in intraspecific communication. Here, we used gas chromatography-mass spectrometry (GC-MS) to describe the lipophilic chemicals from the dark ventral patch of males from different popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 60 publications
2
25
0
Order By: Relevance
“…Previous studies, using genetic and behavioural tools, have shown clear differences in the degree of male-male competition 30 and the consequences in the transmission of genetic variability to the next generation 29 between these two social environments. Our results are also in agreement with the effects of male competition in these same Iberian red deer populations on the dark ventral patch, that may be modulated in the short term by urination, changing its size (Carranza et al, under review) and its chemical constituents 31 . Predicted means of antler length (cm, ± se) of 2 and 3 year-old males in estates with high (HC) and low (LC) male-male competition for mating opportunities.…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies, using genetic and behavioural tools, have shown clear differences in the degree of male-male competition 30 and the consequences in the transmission of genetic variability to the next generation 29 between these two social environments. Our results are also in agreement with the effects of male competition in these same Iberian red deer populations on the dark ventral patch, that may be modulated in the short term by urination, changing its size (Carranza et al, under review) and its chemical constituents 31 . Predicted means of antler length (cm, ± se) of 2 and 3 year-old males in estates with high (HC) and low (LC) male-male competition for mating opportunities.…”
Section: Discussionsupporting
confidence: 90%
“…Antler size is positively correlated with winning fights and mating success (Clutton-Brock et al 1982;Malo et al 2009). In addition to the widely studied antlers, there is another nonpermanent sexual trait in male Iberian red deer: the dark ventral patch (Martín et al 2014;de la Peña et al, 2019;Carranza et al in preparation). The size of this trait reveals the dominance rank and reproductive effort that a male has made in the most recent rutting season (Martín et al 2014;de la Peña et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has shown that, due to the pigmentation mechanism mediated by a urine excretion metabolite of norepinephrine [ 28 ], the dark ventral patch size may contribute to rival assessment during male-male competition as well as reveal the reproductive effort of a male during the current rutting season. In addition, previous studies on the lipid compounds impregnating the hairs of this area show that this character may act as a chemical sexual signal [ 29 ] modulated by the competitive context [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…the intrasexual competition level of the population. Previous studies showed that the chemical scent constituents in this trait are mediated by the social environment [ 30 ]. In this work we did not find evidence of the role of male-male competition per se on the dark ventral patch expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation